New drugs are not enough: addressing social determinants as a critical component of drug-resistant TB care - D. Giovenco; N.S. Shah; K. Ansorge; D. Operario; N.R. Gandhi (IJTLD Open)
The global fight against drug-resistant TB (DR-TB) is hindered by an underappreciation of the importance of the social determinants of TB. Although shorter, all-oral regimens have improved treatment options, high rates of non-adherence persist due to stigma, financial hardship and other healthcare access barriers. Lessons from HIV highlight the importance of addressing structural and psychosocial factors in treatment management. Consideration of an ecosocial framework integrating biological, social and environmental perspectives is critical for effective DR-TB interventions. A paradigm shift toward patient-centered care and social support strategies is urgently needed to improve treatment outcomes and advance global efforts to eradicate DR-TB.